First principles treatment of structural, optical, and thermoelectric properties of Li7MnN4 as electrode for a Li secondary battery. (January 2015) - Khan, Wilayat; Reshak, A.H.
Graphical abstract: Abstract: The electronic structure, electronic charge density and linear optical properties of the metallic Li7 MnN4 compound, having cubic symmetry, are calculated using the full potential linearized augmented plane wave (FP-LAPW) method. The calculated band structure and density of states using the local density, generalized gradient and Engel–Vosko approximations, depict the metallic nature of the cubic Li7 MnN4 compound. The bands crossing the Fermi level in the calculated band structure are mainly from the Mn-d states with small support of N-p states. In addition, the Mn-d states at the Fermi level enhance the density of states, which is very useful for the electronic transport properties. The valence electronic charge density depicts strong covalent bond between Mn and two N atoms and polar covalent bond between Mn and Li atoms. The frequency dependent linear optical properties like real and imaginary part of the dielectric function, optical conductivity, reflectivity and energy loss function are calculated on the basis of the computed band structure. Both intra-band and inter-band transitions contribute to the calculated optical parameters. Using the BoltzTraP code, the thermoelectric properties like electrical and thermal conductivity, Seebeck coefficient, power coefficient and heat capacity of the Li7 MnN4 are also calculated as a function of temperature and studied.